Sustainability Accounting Measuring and Reporting Environmental Costs - Sultan, Karam Hshim; Ali, Nidhal Jasm Mohammed; Mohammed, Mohammed Talaat; Salman, Alaa Jassim (Journal of Ecohumanism, 2024)
Background: The increasing awareness of environmental sustainability has led to a growing need for businesses to measure and report their environmental costs. Sustainability accounting, which integrates financial and environmental data, provides a comprehensive framework for assessing the ecological impact of business operations. This field is pivotal for promoting transparency and accountability in environmental stewardship. Objective: This study aims to explore the methodologies and practices involved in measuring and reporting environmental costs within the framework of sustainability accounting. It seeks to identify the benefits and challenges faced by organizations in implementing these practices and to propose solutions for enhancing their effectiveness. Methods: A mixed-method approach was adopted, combining quantitative data analysis of environmental costs reported by 50 companies with qualitative interviews of 30 key stakeholders. The quantitative analysis involved examining financial statements and sustainability reports from 2018 to 2022, while the qualitative component gathered insights from managers and accountants on the practical aspects of sustainability accounting. Results: The study revealed significant variability in the measurement and reporting practices of environmental costs. Companies with established sustainability accounting frameworks demonstrated a 25% improvement in environmental performance and a 30% increase in transparency. However, challenges such as lack of standardized reporting guidelines and inadequate integration of environmental costs into financial decision-making were identified. Conclusion: Sustainability accounting is crucial for fostering corporate accountability and environmental stewardship. The study highlights the need for standardized guidelines and enhanced integration of environmental costs into financial practices. Addressing these challenges can lead to more accurate reporting and better decision-making, ultimately contributing to sustainable business practices and environmental conservation.